CEO Overconfidence and Corporate Innovation Outcomes: Evidence From China - Li, Zhongze; Zhang, Yi (Frontiers in Psychology, 2022)
This study examines how CEO overconfidence can influence the quantity, quality and direction of corporate innovation using Chinese firms for the period 2009-2016. Our results suggest that overall, CEO overconfidence has a positive impact on firm innovation productivity. Furthermore, this effect is significant for Chinese non-SOEs but not for Chinese SOEs. Specifically, an overconfident CEO can facilitate firm innovation in new technological areas but not in the firm’s existing areas. Additionally, we find that internal controls can regulate the relationship between CEO overconfidence and innovation. Interestingly, when the internal control level is too high or too low, the correlation between CEO overconfidence and innovation productivity is not significant.